(untitled) (Research, Society and Development, 2022)
Objective: Understand the relationship between fibromyalgia and a genetic variant of the VDR gene, called Cdx2 that encodes the vitamin D receptor, besides evaluating the association of clinical characteristics from the study participants with genotypic and allelic variants of the VDR gene. Methods: This is a case-control, cross-sectional, quantitative, and experimental study, that recruited 65 individuals, however, due to the exclusion factors applied, only 62 participated effectively, 33 with FM and 29 in the control group. 5 questionnaires were applied to those with disease and only 1 to those without. The polymorphism of Cdx2, promotes a G/A exchange, in 12q13.11, found through the qPCR. Results: By analyzing the genotypes, 54.8% (34/62) of the participants were GG, 32.3% (20/62) GA and the AA genotype was present in 12.9% (8/62). Among the participants, 83.9% (52/62) were female and 74.2% (46/62) were white. The genetic variant, Cdx2, was statistically correlated with FM (p=0.004), where 66.7% of patients with FM had the GG genotype, moreover the GG/GA genotype had 12,6 chances of developing FM (OR = 12,57; IC95%: 1,465-107,889; P=0.001) if compare with the genotype AA. Conclusion: The polymorphism of Cdx2 (AA) increases the expression of the receptor, inhibits the Th1 response and activates the Th2, also improves the response to vitamin D and acts as a protective factor for the individual without the disease.